Honduras in pictures - Weddle Ken; Lerner Publications Company Geography Dept (Minneapolis : The Company, 1999)
Text and pictures provide a close look at the land, people, history, government, and economy of this Central American nation.
Rev. ed. of: Honduras in pictures / prepared by Ken Weddle.
Includes index.
Keywords: Honduras; Honduras